Metallographic analysis on low temperature gas nitriding process of AISI 316 stainless steel / Muzafar Aminon - Aminon, Muzafar (2010)
Stainless steel is a commonly used metal in industrial factory. Stainless steel is the most common form of steel provides material properties that are acceptable for many applications. This thesis describes a study on the effect of thermochemical process on microstructure of austenitic stainless steel by low temperature nitriding process. For this project, there were 15 of specimens prepared by fabricating the stainless steel to square shape (40mmx40mmx4mm) prior to nitriding process. For the heat treatment process, specimen is exposed to nitrogen gas at low temperatures 400°C to 500°C for 1 hour to 7 hours holding time using fluidized bed furnace. Treated samples were characterized by means of morphological analysis, in order to investigate the influence of temperature and treatment time on the microstructure, by using scanning electron microscopy and image analyzer microscope. Moreover, the results were compared with those observed for untreated samples. The modified surface layer of the nitrided samples consists mainly of the S-phase and according to metallographic technique analysis; it seems to be modification of the austenite matrix. All nitride samples show a strange surface morphology. X-ray diffraction analysis shows that for the samples nitrided, besides the S phase, small chromium nitride precipitates are present at the surface, while using higher treatment temperatures both chromium (CrN) and iron (y'-Fe4N) nitrides precipitate on surface of samples.